Evaluasi Kekuatan Rel UIC54 Menggunakan Metode Beam On Elastic Foundation (BOEF) - prativi, ayu; Adi, Wahyu Tamtomo (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2020)
In Indonesia, the dimensions of the rail steel profile have been determined by Minister of Transportation Regulation Number 60 of 2012. The commonly rail which used for 1067mm railway width is the rail type UIC54. However, the determination of rail profile type in Indonesia has not been equipped with an analysis of the rail profile strength to support the load acting on it. Thus, this journal will discuss the calculation of the UIC54 rail strength analysis to support locomotive loads of CC 203, CC 205, and CC 206. The calculation is using Beam on Elastic Foundation (BOEF) method which assumes rail behavior as a continuous beam that support loads above an elastic foundation. The value of UIC rail strength is written in the form of safety factors (SF). The calculation results show that the value of the most critical rail SF to support locomotive loads CC 203, CC 205, and CC 206 are 10.94; 8.93; and 9.67. The results of the rail strength calculation shows that the UIC54 rail is very strong in resisting the dynamic load of the locomotive and its cross section is too large to support the dynamic wheel load of the locomotive.